Flame retardant phase change material and preparation method thereof

By using polyethylene glycol in organic phase change materials to react with phosphorus pentoxide, and adding expanded graphite and phosphorus-based flame retardant to cross-link with amino flame retardant, forming polymers, the high temperature of the material is solved The problems of flammability and leakage are significantly improved, and the flame retardant performance and thermal stability are achieved, achieving efficient flame retardant effects.

CN118652534BActive Publication Date: 2024-12-27CATARC AUTOMOTIVE TEST CENT (GUANGZHOU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411147787.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-27
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

Organic phase change materials are flammable and leaky at high temperatures. Traditional support frame materials are flammable and have limited addition of flame retardant, resulting in poor flame retardant performance, and flame retardant settlement and aggregation leads to a decrease in flame retardant performance of the material.

Method used

By reacting polyethylene glycol with phosphorus pentoxide to form polyethylene glycol phosphate as a skeleton, adding expanded graphite and phosphorus-based flame retardant, cross-linking and curing with the amino-containing flame retardant to form a polymer, and strengthening The flame retardant properties and rigidity of the material.

Benefits of technology

The flame retardant performance and thermal stability of organic phase change materials are significantly improved, and the problems of high temperature flammability and leakage are avoided, forming a stable expanded carbon layer barrier flame, achieving efficient flame retardant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118652534B_ABST
    Figure CN118652534B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of organic phase change materials, and specifically discloses a flame retardant phase change material and a preparation method thereof. The flame retardant phase change material prepared by the method of the present invention has intrinsic flame retardant properties, and is not easy to collapse or leak. The flame retardant phase change material of the present invention, when burning, because it has a phase change skeleton of polyethylene glycol segments, absorbs a certain amount of heat through phase change to delay the occurrence of combustion; and during the combustion process, it can produce refractory gas to dilute the oxygen concentration in the ignition area; at the same time, because it has a phosphorus-containing acid source, it enhances the compactness of the residual carbon generated in the condensed phase, forming a more stable expanded carbon layer, effectively blocking the flame and oxygen from entering the interior of the material, hindering the continued spread of the flame, and achieving a flame retardant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic phase change materials, and in particular relates to a flame retardant phase change material and a preparation method thereof. Background Art

[0002] In recent years, organic phase change materials have been widely used in electronic devices and energy storage fields. Therefore, the requirements for organic phase change materials are getting higher and higher. However, organic phase change materials have problems such as easy leakage and flammability. For example, in core components such as electric vehicle systems and energy storage power stations, a large amount of heat is generated during operation. If the heat is not absorbed and transferred in time, it will cause heat accumulation, causing the temperature of these components to rise; if the temperature rises too high, it may induce thermal runaway of these components, causing material leakage, collapse, and flammability, which poses certain safety hazards.

[0003] In order to improve the thermal cycling performance of phase change materials at high temperatures, polymers such as epoxy resins or styrene-butadiene-styrene block copolymers are often added as supporting skeletons to improve the problem of easy collapse of organic phase change materials. However, these traditional supporting skeleton materials are usually flammable substances, which will further increase the high-temperature flammability risk of organic phase change materials. In order to improve the flame retardant properties of organic phase change materials, some flame retardants are generally added to organic phase change materials by physical mixing. However, due to the differences in their own properties, there are compatibility issues in the blending of flame retardants and organic phase change materials, which limits the amount of flame retardants added and the flame retardant properties. Moreover, because the flame retardant and the organic phase change material are physically blended, the flame retardant will settle and aggregate as the material is used, resulting in a significant decrease in the flame retardant properties of the material or even flame retardant failure. Summary of the invention

[0004] In view of the problems of the phase change materials involved in the above-mentioned prior art, such as easy leakage, collapse and poor flame retardancy, the present invention provides a flame retardant phase change material and a preparation method thereof.

[0005] To achieve the above purpose, the following technical solutions are specifically included:

[0006] A method for preparing a flame retardant phase change material comprises the following steps:

[0007] (1) melting polyethylene glycol, adding phosphorus pentoxide to react, and obtaining polyethylene glycol phosphate;

[0008] (2) melting the polyethylene glycol phosphate, adding expanded graphite and phosphorus flame retardant, and mixing evenly;

[0009] (3) Adding an amino-containing flame retardant to carry out cross-linking and curing to obtain the flame-retardant phase change material.

[0010] In the method of the present invention, first, molten polyethylene glycol and phosphorus pentoxide are subjected to an esterification reaction to generate polyethylene glycol phosphate, wherein the hydroxyl groups on the polyethylene glycol and phosphorus pentoxide as a phosphorylating agent are subjected to an esterification reaction to generate phosphate bonds. Polyethylene glycol phosphate, as a precursor of the flame-retardant phase change material of the present invention, is the basic skeleton of the overall material, and due to the phosphate bonds in the polyethylene glycol phosphate, the polyethylene glycol phosphate has certain flame retardant properties, thereby increasing the flame retardant properties of the material; secondly, expanded graphite and phosphorus-based flame retardants are added to the molten polyethylene glycol phosphate, and the expanded graphite has a good adsorption effect. The hydroxyl-containing polyethylene glycol phosphate is enriched through the adsorption effect of the expanded graphite, providing stable conditions for the hydroxyl groups on the polyethylene glycol phosphate to react quickly with the amino groups of the flame retardant in the next step. At the same time, the expanded graphite has flame retardant properties, which can further increase the flame retardant properties. Increase the flame retardancy of the material; here, adding a phosphorus-based flame retardant can make the phosphorus-based flame retardant combine more evenly with other materials, thereby increasing the flame retardant properties of the material; finally, adding an amino-containing flame retardant, because there is a basis of expanded graphite-enriched polyethylene glycol phosphate in the system, the local concentration of hydroxyl groups increases, and the hydroxyl groups of the polyethylene glycol phosphate quickly cross-link with the amino groups in the amino-containing flame retardant to quickly generate a high molecular polymer. At the same time, the amino group in melamine is a nucleophilic group, which can also attack the phosphate group in the polyethylene glycol phosphate, thereby successfully accessing melamine to form a high molecular polymer with a three-dimensional network structure. Phosphorus pentoxide and amino-containing flame retardants are both flame-retardant substances. Polyethylene glycol has good flame retardant properties after reacting with phosphorus pentoxide and amino-containing flame retardants in sequence. The high molecular polymer cooperates with phosphorus-based flame retardants and expanded graphene to significantly increase the flame retardant properties of organic phase change materials, improve the problems of high temperature flammability and easy leakage of organic phase change materials, and because the high molecular polymer has a larger molecular weight, it can increase the overall rigidity of the material with phosphorus-based flame retardants and expanded graphite, and improve the problem of high temperature collapse of organic phase change materials.

[0011] Preferably, in step (1), the molar ratio of polyethylene glycol to phosphorus pentoxide is 1:(0.9-1.2); the reaction temperature is 90-130° C., and the reaction time is 1-5 h.

[0012] Preferably, in step (1), the molecular weight of the polyethylene glycol is 1000-4000.

[0013] Preferably, in step (1), the polyethylene glycol includes at least one of polyethylene glycol 1500, polyethylene glycol 2000, and polyethylene glycol 4000.

[0014] By using polyethylene glycol with the above molecular weight, the flame-retardant phase change material can obtain a high enthalpy value while maintaining the melting point at an appropriate phase change temperature to meet actual application requirements.

[0015] Preferably, in step (2), the mass ratio of the polyethylene glycol phosphate, expanded graphite and phosphorus-based flame retardant is polyethylene glycol phosphate: expanded graphite: phosphorus-based flame retardant = (60-80): (1-3): (5-10).

[0016] Preferably, in step (2), the phosphorus-based flame retardant includes at least one of ammonium polyphosphate and aluminum hypophosphite.

[0017] Preferably, in step (2), the uniform mixing method is stirring, the stirring rate is 500-1000 r / min, and the stirring time is 0.5-1.5 h.

[0018] Preferably, in step (3), the amino-containing flame retardant includes melamine.

[0019] The present invention is to add expanded graphite to enrich the molten polyethylene glycol phosphate after the molten polyethylene glycol and phosphorus pentoxide are fully reacted, and then add melamine to fully react with it to synthesize an intrinsic flame retardant phase change material. In the intrinsic flame retardant phase change skeleton material, the polyethylene glycol segment provides latent heat characteristics, the access of the phosphoric acid group and melamine gives the phase change material a flame retardant property, and at the same time, a melamine-polyethylene glycol phosphate resin is formed by cross-linking of melamine, and the overall flame retardancy is improved by the synergistic flame retardant effect of adding a phosphorus flame retardant, thereby comprehensively realizing the flame retardancy and phase change performance of the phase change material.

[0020] Preferably, in step (3), the temperature of the cross-linking and curing is 65-80° C., and the time of the cross-linking and curing is less than 15 min.

[0021] Preferably, in step (3), a stirring process is performed before cross-linking and curing, and the stirring time is 2-5 minutes.

[0022] Preferably, in step (3), the mass ratio of the polyethylene glycol phosphate to the amino-containing flame retardant is (60-80):(10-30).

[0023] Preferably, in step (3), stirring is performed before cross-linking and curing, and the stirring time is 2-10 minutes.

[0024] Compared with the prior art, the present invention has the following beneficial effects: the flame-retardant phase-change material prepared by the method of the present invention has intrinsic flame-retardant properties, and is not easy to collapse or leak. The flame-retardant phase-change material of the present invention, when burning, will absorb a certain amount of heat through phase change to delay the occurrence of combustion because it has a phase-change skeleton of polyethylene glycol segments; and during the combustion process, it can produce refractory gas to dilute the oxygen concentration in the ignition area; at the same time, because it has a phosphorus-containing acid source, it enhances the compactness of the residual carbon generated in the condensed phase, forming a more stable expanded carbon layer, effectively blocking the flame and oxygen from entering the interior of the material, hindering the continued spread of the flame, and achieving a flame-retardant effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the flame retardant phase change material in Example 1.

[0026] Figure 2 This is a reaction process diagram for preparing the flame retardant phase change material in Comparative Example 1, wherein the timing starts when all melamine is added (i.e., the illustration on the far left), and actual pictures are taken at the start, 1h, 2h, 3h, 4h, and 5h time nodes, respectively. At 5h, liquid is still present in the system and it is not completely cured.

[0027] Figure 3 This is a reaction process diagram for preparing the flame retardant phase change material in Example 2, wherein the timing starts when all melamine is added (i.e., the illustration on the far left), and actual pictures are taken at the start, 30s, 60s, 90s, 120s, and 135s time nodes, respectively. At 135s, the system is completely cured, and the product is uniformly black (in the illustration at the 135s time node, the black part is the product, and the white part is the weighing paper placed at the bottom when the product is weighed).

[0028] Figure 4 This is a diagram showing the leakage phenomenon of the flame-retardant phase change material in Example 2 when continuously heated at 250°C.

[0029] Figure 5 This is a test result diagram of the vertical combustion test of the flame retardant phase change material in Comparative Example 2.

[0030] Figure 6 This is a diagram showing the vertical combustion test results of the flame retardant phase change material in Example 1.

[0031] Figure 7 This is a diagram showing the vertical combustion test results of the flame retardant phase change material in Example 2.

[0032] Figure 8 This is a graph showing the phase change enthalpy test results of the flame retardant phase change material in Example 2.

[0033] Fig. 9The figure is a Fourier transform infrared spectroscopy test result diagram of pure polyethylene glycol and the flame retardant phase change material prepared in Example 2, wherein the black curve in the figure represents the IR spectrum of polyethylene glycol, and the red curve (polyethylene glycol phosphate-melamine) represents the IR spectrum of the flame retardant phase change material prepared in Example 2. DETAILED DESCRIPTION

[0034] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified. Among them, the polyethylene glycol used in the following examples is polyethylene glycol with a molecular weight of 2000.

[0035] Example 1

[0036] A method for preparing a flame retardant phase change material comprises the following steps:

[0037] (1) 100 g of polyethylene glycol was melted in a magnetic stirring oil bath at 90° C. When the polyethylene glycol was completely melted, the temperature was maintained and phosphorus pentoxide in a molar ratio of 1:1 to the polyethylene glycol was added under stirring at 800 r / min to react to obtain polyethylene glycol phosphate;

[0038] (2) 70 g of the above-synthesized polyethylene glycol phosphate was added to an oil bath and melted at 70° C. The temperature was maintained at 70° C. Then 2 g of expanded graphite and 8 g of aluminum hypophosphite were added and stirred at a stirring rate of 800 r / min.

[0039] (3) Maintaining the temperature, add another 20 g of melamine and stir rapidly at 800 r / min to obtain a flame-retardant phase change material. The mixture is poured into a mold and cross-linked and cured at 70°C to obtain a flame-retardant phase change material.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that the phosphorus-based flame retardant in this embodiment adopts ammonium polyphosphate, and the specific steps are as follows:

[0042] (1) 100 g of polyethylene glycol was melted in a magnetic stirring oil bath at 90° C. When the polyethylene glycol was completely melted, the temperature was maintained and phosphorus pentoxide in a molar ratio of 1:1 to the polyethylene glycol was added under stirring at 800 r / min to react to obtain polyethylene glycol phosphate;

[0043] (2) 70 g of the above-synthesized polyethylene glycol phosphate was added to an oil bath and melted at 70° C. The temperature was maintained at 70° C. Then 2 g of expanded graphite and 8 g of ammonium polyphosphate were added and stirred at a stirring rate of 800 r / min.

[0044] (3) Maintain the temperature and add another 20g of melamine, stirring rapidly at 800r / min. Attention should be paid to the speed of adding melamine to avoid too fast reaction between melamine and polyethylene glycol phosphate, which will lead to uneven mixing and destroy the continuity of the phase change material. Pour it into the mold and cross-link and cure it at 70℃. The process diagram is shown in the attached figure. Figure 3 As shown, a flame retardant phase change material is obtained.

[0045] Comparative Example 1

[0046] The difference between this comparative example and Example 1 is that no expanded graphite is added in this example, and the specific steps are as follows:

[0047] (1) 100 g of polyethylene glycol was melted in a magnetic stirring oil bath at 90° C. When the polyethylene glycol was completely melted, the temperature was maintained and phosphorus pentoxide in a molar ratio of 1:1 to the polyethylene glycol was added under stirring at 800 r / min to react to obtain polyethylene glycol phosphate;

[0048] (2) 70 g of the polyethylene glycol phosphate synthesized above was added to an oil bath and melted at 70°C, and then 8 g of ammonium polyphosphate was added and stirred at a stirring rate of 800 r / min.

[0049] (3) Maintain the temperature and add another 20g of melamine, stirring rapidly at 800r / min. Attention should be paid to the speed of adding melamine to avoid too fast reaction between melamine and polyethylene glycol phosphate, which will lead to uneven mixing and destroy the continuity of the phase change material. Pour into the mold and cross-link and cure at 70℃. The process diagram is shown in the attached figure. Figure 2 As shown, there is still some liquid after 5 hours, and the flame retardant phase change material is obtained after complete solidification.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 1 is that no phosphorus-based flame retardant is added in this comparative example, and the specific steps are as follows:

[0052] (1) 100 g of polyethylene glycol was melted in a magnetic stirring oil bath at 90° C. When the polyethylene glycol was completely melted, the temperature was maintained and phosphorus pentoxide in a molar ratio of 1:1 to the polyethylene glycol was added under stirring at 800 r / min to react to obtain polyethylene glycol phosphate;

[0053] (2) 70 g of the above-synthesized polyethylene glycol phosphate was added to an oil bath and melted at 70° C. The temperature was maintained at 70° C. Then 2 g of expanded graphite was added and stirred at a stirring rate of 800 r / min.

[0054] (3) Maintaining the temperature, add another 20 g of melamine and stir rapidly at 800 r / min for 5 min. Attention should be paid to the speed of adding melamine to avoid too fast reaction between melamine and polyethylene glycol phosphate, which will lead to uneven mixing and destroy the continuity of the phase change material. Pour the mixture into a mold and perform cross-linking and curing at 70 °C to obtain a flame-retardant phase change material.

[0055] Fourier transform infrared spectroscopy (IR) was performed on pure polyethylene glycol and the flame retardant phase change material prepared in Example 2. The test results are shown in the attached figure. Fig. 9 As shown. Through Fourier infrared spectroscopy analysis, it can be found that the flame retardant phase change material has a -1 The characteristic absorption peak of methylene bridge appears at 1550cm -1 The characteristic vibration peak of the triazine ring at 816 cm indicates that melamine participates in the reaction. The IR test results confirm that the amino group of melamine and the hydroxyl group of polyethylene glycol phosphate undergo cross-linking reaction, and the amino group in melamine is a nucleophilic group, which can also attack the phosphate group in polyethylene glycol phosphate, thereby successfully connecting melamine to form a high molecular polymer with a three-dimensional network structure. In addition, at 816 cm -1 and 590cm -1 The absorption peaks at are the asymmetric vibrations of PO and P-OH, indicating that P2O5 is introduced into the molecular chain of the flame retardant phase change material. Among them, P2O5, as a phosphorylating agent, reacts with the hydroxyl group in polyethylene glycol to form a phosphate bond to generate polyethylene glycol phosphate.

[0056] The flame-retardant phase-change material of Example 2 was subjected to an anti-leakage test to verify whether the anti-leakage performance was improved to verify whether melamine was successfully grafted onto the polyethylene glycol phosphate. The anti-leakage test of the phase-change material was completed by placing the phase-change material on a constant temperature heating table set at 250°C, observing and recording the appearance and mass changes before and after the anti-leakage test at regular intervals. The thermal stability of the phase-change material was characterized by the mass change curve of the phase-change material in the anti-leakage test. The mass change of the phase-change material is shown in the attached figure. Figure 4 As shown, it can be seen that the quality of the flame retardant phase change material sample of the present invention in the anti-leakage test is almost leak-free at high temperature, that is, the intrinsic flame retardant phase change skeleton is successfully synthesized, and the quality retention rate is still above 98% after continuous heating at 250°C for more than 5 hours, indicating that the high temperature resistance of the intrinsic flame retardant phase change skeleton material prepared by the present invention is greatly improved. It can be seen that melamine in the flame retardant phase change material of the present invention is successfully grafted on polyethylene glycol phosphate.

[0057] A small amount of the flame retardant phase change material sample prepared in Example 2 was taken to test the phase change enthalpy value. The test results are as follows: Figure 7 As shown; the results show that the flame retardant phase change material of the present invention has a phase change latent heat value of 73J / g, still has the latent heat characteristics of the original polyethylene glycol, and has the characteristics of intrinsic phase change.

[0058] The reaction process diagrams at different time periods in Comparative Example 1 and Example 2 are shown in the attached diagrams. Figure 2-3 It can be observed that when expanded graphite exists, due to the presence of expanded graphite-enriched polyethylene glycol phosphate in the system, the local concentration of hydroxyl groups increases, and the hydroxyl groups of polyethylene glycol phosphate rapidly cross-link with the amino groups in melamine to quickly generate melamine-polyethylene glycol phosphate resin, which can significantly accelerate the reaction process and shorten the reaction time.

[0059] The flame retardant phase change material prepared in Example 2 was tested by scanning electron microscopy (SEM), and the results are shown in the attached figure. Figure 1 As shown. Figure 1 It can be observed that the flame retardant phase change material prepared by the present invention has uniform components and a dense structure.

[0060] The flame retardant phase change material prepared in the above embodiment 1-2 was subjected to a vertical combustion test. The vertical combustion test refers to the UL-94-2016 test standard. The flame retardant phase change material sample was subjected to two ignition tests. After the first ignition test, it was extinguished within 10 seconds, and after the second ignition, it was extinguished within 30 seconds, and there was no burning drop, which was the highest rating V-0 level; the flame retardant phase change material sample was subjected to two ignition tests. The flame extinguishing time was 60 seconds, and the flame droplets did not ignite the cotton, which met the UL-94 test V-1 standard. The test results are shown in the attached Figure 5-7 .

[0061] Conventional phase change materials are flammable and will continue to burn if ignited, so they cannot be rated UL-94. Figure 5 The vertical combustion test result of the flame retardant phase change sample in Comparative Example 2 is shown in FIG. 1 ; the vertical combustion test refers to the UL-94 test standard. The sample in Comparative Example 2 is extinguished within 1 second after the first ignition and breaks after 6 seconds after the second ignition, but the dripping material does not ignite the cotton, which meets the UL-94 test V-1 standard; Attachment Figure 6 The result of the vertical combustion test of the flame-retardant phase change material with aluminum hypophosphite added to Example 1 is shown. The flame retardant phase change material is extinguished within 1 second after the first ignition and extinguished after 2 seconds after the second ignition, meeting the UL-94 test V-0 standard. Figure 7The result graph of the vertical combustion test of the flame-retardant phase change material with ammonium polyphosphate added for synergistic flame retardancy in Example 2 is that the flame retardant is instantly extinguished within 1 second after the first ignition, and is extinguished after 2 seconds after the second ignition, meeting the UL-94 test V-0 standard; therefore, it can be proved that the flame retardant performance of the intrinsic flame-retardant solid-solid phase change material of the present invention is greatly improved compared with the traditional phase change material, and by combining with ammonium polyphosphate or aluminum hypophosphite, the flame retardant grade can be increased to V-0, which has a synergistic effect.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a flame retardant phase change material, characterized in that: The steps include: (1) melting polyethylene glycol, adding phosphorus pentoxide to react, and obtaining polyethylene glycol phosphate; the molar ratio of the polyethylene glycol to the phosphorus pentoxide is 1:(0.9-1.2); (2) melting the polyethylene glycol phosphate, adding expanded graphite and a phosphorus-based flame retardant, and mixing them evenly; the phosphorus-based flame retardant comprises at least one of ammonium polyphosphate and aluminum hypophosphite; (3) Adding an amino-containing flame retardant for cross-linking and curing to obtain the flame-retardant phase change material; the cross-linking and curing time is less than 15 minutes; the amino-containing flame retardant is melamine.

2. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: In step (1), the reaction temperature is 90-130° C., and the reaction time is 1-5 h.

3. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: In step (1), the molecular weight of the polyethylene glycol is 1000-4000.

4. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: In step (2), the mass ratio of the polyethylene glycol phosphate, expanded graphite and phosphorus-based flame retardant is polyethylene glycol phosphate: expanded graphite: phosphorus-based flame retardant = (60-80): (1-3): (5-10).

5. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: In step (2), the uniform mixing method is stirring, the stirring rate is 500-1000 r / min, and the stirring time is 0.5-1.5 h.

6. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: In step (3), the temperature of the cross-linking and curing is 65-80°C.

7. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: In step (3), the mass ratio of the polyethylene glycol phosphate to the amino-containing flame retardant is (60-80):(10-30).

8. A flame retardant phase change material obtained by the method for preparing a flame retardant phase change material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method for phosphate ester flame retardant toughening phenolic foam material

    CN102746613A

  • Phase-change heat absorption and intumescent flame retardant steel structure fireproof paint and preparation method thereof

    CN108559359A

  • Phase change composite material as well as preparation method and application thereof

    CN115466600A

  • Organic phase change material bis (polyethylene glycol) methylphosphonate as well as preparation method and application thereof

    CN118307766A

  • Articles containing precisely branched functional polymeric phase change materials

    US20120225290A1